Phosphoproteome Analysis in Immune Cell Signaling. (16th September 2020) - Rathore, Deepali; Nita‐Lazar, Aleksandra
Abstract: Immune cell signaling is largely regulated by protein phosphorylation. Stimulation of toll‐like receptors (TLRs) by pathogen‐associated ligands drives the cascade of immune response, which can be influenced by differences in phosphoprotein abundance. Therefore, the analysis of phosphorylation signatures at a global level is central to understanding the complex and integrated signaling in macrophages upon pathogen attack. Here, we describe a mass spectrometry‐based approach to identify and quantify phosphoproteome changes in response to the stimulation of TLR2, TLR4, and TLR7 with immune‐response inducing ligands in cultured immune cells. This review will focus on the TLR stimulation of mouse macrophages as an example; however, the technique is applicable to any immortalized immune cell and any soluble stimuli. The methodology includes protocols for metabolic labeling of immune cells (stable isotope labeling of amino acids in cell culture, i.e., SILAC); ligand‐initiated stimulation of immune receptors followed by cell lysis; in‐solution trypsin digestion of proteins and enrichment of the resulting peptide mix for collecting phosphopeptides, which are then analyzed by high‐resolution LC‐MS/MS (liquid‐chromatography tandem mass spectrometry). Published 2020. U.S. Government. Basic Protocol 1 : SILAC labeling of mouse macrophages Basic Protocol 2 : Stimulation, cell lysis and Western Blotting Basic Protocol 3 : Trypsin digestion, fractionation and phosphopeptide enrichment Basic Protocol 4 : Quantitative mass spectrometry Alternate Protocol : Culturing SILAC‐labeled cells from frozen mouse macrophages cells